A Scoping Review of Behavior Change Interventions to Decrease Health Care Disparities for Patients With Disabilities in a Primary Care Setting: Can Social Marketing Play a Role?. (March 2021) - Makris, Angela; Khaliq, Mahmooda; Perkins, Elizabeth
Background: One in four Americans have a disability but remain an overlooked minority population at risk for health care disparities. Adults with disabilities can be high users of primary care but often face unmet needs and poor-quality care. Providers lack training, knowledge and have biased practices and behaviors toward people with disabilities (PWD); which ultimately undermines their quality of care. Focus of the Article: The aim is to identify behavior change interventions for decreasing health care disparities for people with disabilities in a healthcare setting, determine whether those interventions used key features of social marketing and identify gaps in research and practice. Research Question: To what extent has the social marketing framework been used to improve health care for PWD by influencing the behavior of health care providers in a primary health care setting? Program Design/Approach: Scoping Review. Importance to the Social Marketing Field: Social marketing has a long and robust history in health education and public health promotion, yet limited work has been done in the disabilities sector. The social marketing framework encompasses the appropriate features to aligned with the core principles of the social model of disability, which espouses that the barriers for PWD lie within society and not within the individual. Incorporating elements of the social model of disability into the social marketing framework could foster a better understanding of the separation of impairment and disability in the healthcare sector and open a new area of research for the field. Results: Four articles were found that target primary care providers. Overall, the studies aimed to increase knowledge, mostly for clinically practices and processes, not clinical behavior change. None were designed to capture if initial knowledge gains led to changes in behavior toward PWD. Recommendations: The lack of published research provides an opportunity to investigate both the applicability and efficacy of social marketing in reducing health care disparities for PWD in a primary care setting. Integrating the social model of disability into the social marketing framework may be an avenue to inform future interventions aimed to increase health equity and inclusiveness through behavior change interventions at a systems level.